Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1055/s-2007-981542
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Apoptosis and DNA Damage Induced by Alpinia galanga Rhizome Extract

Abstract: Alpinia galanga, or galangal, has been a popular condiment used in Thai and Asian cuisine for many years. However, relatively little is known of the potential beneficial or adverse health effects of this spice. This study was conducted to analyze the capacity of galangal extract to induce cytotoxicity and DNA damage in six different human cell lines including normal and p53-inactive fibroblasts, normal epithelial and tumour mammary cells and a lung adenocarcinoma cell line. We deliberately focused on treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…To assess the effects of DCA on a more aggressive tumor model, we injected rats with CRL-2335 mammary carcinoma cells, a cell line that has low expression of p53 37 (Supplementary Figure 1b). When injected with the same number of cells, these animals developed larger tumors at a faster rate compared with nSCLC cells, but DCA decreased both the size and the vascularity of these tumors as well ( Supplementary Figures 1c and d).…”
Section: Dca Reduces Tumor Vascularity and Perfusion And Inhibits Hifmentioning
confidence: 99%
“…To assess the effects of DCA on a more aggressive tumor model, we injected rats with CRL-2335 mammary carcinoma cells, a cell line that has low expression of p53 37 (Supplementary Figure 1b). When injected with the same number of cells, these animals developed larger tumors at a faster rate compared with nSCLC cells, but DCA decreased both the size and the vascularity of these tumors as well ( Supplementary Figures 1c and d).…”
Section: Dca Reduces Tumor Vascularity and Perfusion And Inhibits Hifmentioning
confidence: 99%
“…and applied in local inflammation and skin allergy caused by insect bites or microbes Anti-inflammatory, anti-microbial, anticancer, cytotoxicity (Satish and Dhananjayan, 2003;Mayachiew and Devahastin, 2008;Maungnoi et al, 2007), limonene, 1,8-cineole, camphor, ␣-terpineol, ␣-pinene, camphene, ␤-pinene (Mallavarapu et al, 2002) Aqa: aquatic, Fw: freshwater, C: common, R: rare, ENR: endangered, H: herb, EH: epiphytic herb, Sr: shrub, Tr: tree, Liv: liverworths, Mos: mosses, ST: subtropical, T: tropical, Tm: temperate, RB: root bark, SB: shoot bark, L: leaves, S: seeds, Y/s: young shoot, W/p: whole plant, Rh: rhizome, Tb: tuber. a Use frequency (%) refers to percentage of people that use the plant in relation to total interviewees (N = 70 informants).…”
Section: Rh/60mentioning
confidence: 99%
“…While CAME had no effect on Th cell activation, CDA changed cell morphology of primary CD4+ Th cells upon TCR stimulation (data not shown). Further analysis confirmed that CDA dose‐dependently increased cell apoptosis (Figure 3A) and decreased cell viability of primary CD4+ Th cells (Figure 3C), supporting a pro‐apoptotic activity by acetoxylated phenylpropanoids (Muangnoi et al. , 2007).…”
Section: Resultsmentioning
confidence: 57%